Pendampingan Pengolahan Data Administrasi Kematian Penduduk di Kelurahan Taba Koji Kota Lubuklinggau - Surizka, Apridona; Ade Gia, Aras (Journal of Social Responsibility Projects by Higher Education Forum, 2024)
The sub-district office as government at the local level has an important role in city or district administration. Focusing on local needs, this Subdistrict Office provides important services managing vital documents such as KTPs, Family Cards, birth certificates, and death certificates, as well as providing important services to the community. In this digital era, technology is crucial in helping Subdistrict Offices manage administrative data, including population death data which is the basis for evaluating public health. This community service activity was carried out at the Taba Koji Subdistrict Office, Lubuklinggau City, which aims to develop a system for processing population death data that is structured, accurate, and up to date. Community Service uses information technology to collect data on population deaths which can improve the understanding, knowledge, and skills of Subdistrict staff and RT Heads. Data collection, data security, and the use of information technology are the topics of training and workshops provided to staff and RT heads in the mentoring process. This website-based information system was chosen because it helps the data processing process and increases the effectiveness, efficiency, and accuracy of the data collection program. This community service activity that has an impact on society shows an increase in recording and the use of an integrated system to facilitate reporting and data analysis. Collaboration between the Subdistrict Office, the Head of the RT, and the community is key in the administration of population mortality rates which is an important basis for developing effective health policies.